Dosimetric influence of Flattening Filter (FF) and Flattening Filter Free (FFF) 6 and 10 MV photon beams on Volumetric Modulated Arc Therapy (VMAT) planning in case of prostate carcinoma - Cakir, A.; Akgun, Z.; Saglam, E. Kaytan (Ijrr-Iranian Journal Radiation Res, 2019)
Background: In the treatment of prostate cancer, radiotherapy is the potential to increase second primary cancers such as bladder and rectal cancers. The reasons for this potential are more monitor units (MUs), therefore a larger total body dose because of leakage radiation, a bigger volume of normal tissue is exposed to lower radiation doses. This study was designed to compare the integral dose of using Flattening Filter (FF) and Flattening Filter-Free (FFF) 6 and 10 MV photon beams via volumetric modulated arc therapy (VMAT) for prostate cancer patients. Materials and Methods: Twenty prostate cancer patients were selected retrospectively for this planning study. VMAT plans were developed using the Eclipse (Varian Medical System, Palo Alto, California, USA) Treatment Planning System (TPS) with 6 MV FF, 6 MV FFF, 10 MV FF and 10 MV FFF for each patient. Conformity index (CI), homogeneity index (HI), Integral dose (ID), the volume receiving 5 Gy (V5%) and monitor units (MUs) were compared. Results: The use of 10 MV FF had 206 liter*Gy integral dose to Body-CTV volume. Using 10 MV FFF had 204 liter*Gy integral dose to normal structures. When 10 MV FF or 10 MV FFF were used instead of 6 MV FF and 6 MV FFF integral dose decreased as -7% and -8%, respectively. The dosimetric difference were statistically significant (p<0.05). The use of 10 MV FFF rather than 10 MV FF had limited influence on the integral dose for rectum, bladder, penile bulb and femoral heads. Conclusions: This study showed that high energy photons (10 MV FF, 10 MV FFF) have lower integral dose than low energy photons (6 MV FF, 6 MV FFF). The relationship between low energies, high energies and integral doses is significant, although there is no significant relationship between V5% doses of all energies. In comparison to different treatment plans, we showed that V5% alone did not provide enough information when possible secondary cancer risks were calculated.
Keywords: Integral Radiation Dose; Secondary Cancer; Flattening Filter Free Beam; Volumetric Modulated Arc Therapy; Prostate Cancer; 3-Dimensional Conformal Radiotherapy; Radiation-Therapy; 2nd Cancers; Imrt; Risk; Malignancies; Tomotherapy; Outcomes